2015
DOI: 10.1111/dth.12233
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed intravenous immunoglobulin therapy in refractory ulcerated livedoid vasculopathy: seven cases and a literature review

Abstract: Livedoid vasculopathy (LV) is a thrombotic vasculopathy of the skin of unknown origin. No treatment has been validated in this indication, but case reports demonstrated successful use of intravenous immunoglobulins (IVIg) in LV. We assessed the efficacy and tolerability of 2 g/kg IVIg therapy every month for 2∼3 cycles in patients with refractory LV. We analyzed the efficacy, side effects and recurrence after long-term follow-up (51.9 ± 14.0 months) in seven patients with LV treated with 2 g/kg of IVIg. Mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
1
26
0
1
Order By: Relevance
“…These patients were successfully treated with IVIG: 94% had at least > 50% improvement with 63% going to complete remission. Our data were concordant with previous studies and justified the use of IVIG as a second-line treatment after unsuccessful use of heparin anticoagulation (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These patients were successfully treated with IVIG: 94% had at least > 50% improvement with 63% going to complete remission. Our data were concordant with previous studies and justified the use of IVIG as a second-line treatment after unsuccessful use of heparin anticoagulation (16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 91%
“…Most treatments are based on anticoagulation (1,3). Several retrospective studies and case reports have shown a good response to intravenous immunoglobulins (IVIG) in refractory patients (16)(17)(18)(19). However, in the absence of large prospective controlled studies, there is no recommendation on the dose or duration of medication and as such the optimal therapeutic regimen is unknown.…”
mentioning
confidence: 99%
“…Studies using 2 g/kg of intravenous immunoglobulins (IVIG) every 4 weeks in patients with LV showed resolution of pain in 80% after 2 IVIG cycles and complete remission of ulcerations in 93% of cases with substantial improvement in quality of life. However, there are no clinical trials comparing IVIG efficacy and its impact on quality of life with other treatment options …”
Section: Discussionmentioning
confidence: 99%
“…Treatment options are generally medications targeting thrombo‐occlusive pathogenesis but most of the time they are unable to stop progression or heal the ulcers. Recently, beneficial effects of intravenous immunoglobulins (IVIG) have been demonstrated in case reports, case series and in one open study (Kim, Yoon, Park, Yoon, & Cho, ). We report a retrospective analysis the efficacy of high‐dose IVIG on nine patients with LV for whom resistant to immunosuppressants or could not be prescribed.…”
Section: Introductionmentioning
confidence: 99%